Model–data comparison and data assimilation of mid-Holocene Arctic sea ice concentration - Klein, François; Goosse, Hugues; Mairesse, A.; de Vernal, A. (Climate of the Past, 2014)
The consistency between new quantitative reconstructions of Arctic sea ice concentration based on dinocyst assemblages and the results of climate models has been investigated for the mid-Holocene. The response of the models mainly follows the increase in summer insolation, modulatedto a limited extent by changes in atmospheric circulation. This leads to differences between regions in the models thatare smaller than in the reconstruction. It is, however, impossible to precisely assess the models’ skills because the sea ice concentration changes at the mid-Holocene are small in both the reconstructions and the models and of the same order of magnitude as the reconstruction uncertainty. Performing simulationswith data assimilation using the model LOVECLIM amplifies the regional differences and improves the model–data agreement as expected. This is mainly achieved through a reduction of the southward winds in the Barents Sea and an increase in the westerly winds in the Canadian Basin, inducingan increase in the ice concentration in the Barents and Chukchi seas. This underlines the potential role of atmospheric circulation in explaining the reconstructed changes during the Holocene.